167k views
5 votes
Solve for x: 8x - 3 = 5(2x + 1)​

User Genry
by
4.1k points

2 Answers

7 votes

Answer:

x = - 4

Explanation:

8x - 3 = 5(2x + 1)

8x - 3 = 5 × 2x + 5 × 1

8x - 3 = 10x + 5

8x - 10x = 3 + 5

- 2x = 8

2x = - 8

x = (- 8)/2

x = - 4

Thus, The value of x is -4

-TheUnknownScientist

User Mfussenegger
by
5.6k points
6 votes

Answer:

x = - 4

Explanation:

Given

8x - 3 = 5(2x + 1) ← distribute

8x - 3 = 10x + 5 ( subtract 10x from both sides )

- 2x - 3 = 5 ( add 3 to both sides )

- 2x = 8 ( divide both sides by - 2 )

x = - 4

User Tometchy
by
4.1k points